SISTEM INFORMASI ANALISIS PROFITABILITAS MENGGUNAKAN METODE GPM DAN NPM PADA TOKO SERBAMULIA - Nifita Yapardana; Sudirman; Afifah (STMIK KHARISMA Makassar, 2019)
Serba Mulia Store is a store that sells invitations. Based on the writer's observation, the owner of Multifark Stores in the process of calculating the gross profit and net profit has not done a consistent calculation. The purpose of this research is to design an information system of profitability analysis by using method of gross profit margin and net profit margin at Serba Mulia shop. Research method that will be used to collect data, that is by way of interview to get information directly from Serba Mulia shop. Test method used is Black Box Testing Method. This research produces a program in the form of information system of profitablity analysis by using method of gross profit margin and net profit margin in order to assist Multipurpose Store in analyzing gross profit and earned profit accurately.